2008
DOI: 10.5194/acpd-8-10597-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of the hygroscopic properties of Ca(NO<sub>3</sub>)<sub>2</sub> and internally mixed Ca(NO<sub>3</sub>)<sub>2</sub>/CaCO<sub>3</sub> particles by micro-Raman spectrometry

Abstract: Abstract. To understand and predict the role of mineral aerosol particles processed by reactive nitrogen species in the atmosphere, the hygroscopic properties of both Ca(NO3)2 and Ca(NO3)2-containing mineral particles must be well understood. Using a micro-Raman system, the dehydration and hydration processes of micro-sized individual Ca(NO3)2 and internally mixed Ca(NO3)2/CaCO3 particles were investigated systematically. In addition to accurate quantification of the dependence of water content on relative hum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Krueger et al (2003) found similar deliquescence behavior of Ca(NO 3 ) 2 formed by heterogeneous reaction of CaCO 3 particles with gaseous nitric acid. By Raman-microscopy Liu et al (2008) observed that pure and mixed Ca(NO 3 ) 2 and Ca(NO 3 ) 2 /CaCO 3 microparticles exhibit reversible water uptake and form amorphous hydrates below 7% RH. Rosenoern et al (2008) suggested that the hygroscopic properties of nanocrystalline aerosol particles may also deviate from those of crystalline bulk material, and several studies pointed out that the drying conditions have a strong influence on the morphology of solid aerosol particles (e.g., Mikhailov et al, 2004;Biskos et al, 2006;Rose et al, 2008;Rosenoern et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Krueger et al (2003) found similar deliquescence behavior of Ca(NO 3 ) 2 formed by heterogeneous reaction of CaCO 3 particles with gaseous nitric acid. By Raman-microscopy Liu et al (2008) observed that pure and mixed Ca(NO 3 ) 2 and Ca(NO 3 ) 2 /CaCO 3 microparticles exhibit reversible water uptake and form amorphous hydrates below 7% RH. Rosenoern et al (2008) suggested that the hygroscopic properties of nanocrystalline aerosol particles may also deviate from those of crystalline bulk material, and several studies pointed out that the drying conditions have a strong influence on the morphology of solid aerosol particles (e.g., Mikhailov et al, 2004;Biskos et al, 2006;Rose et al, 2008;Rosenoern et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, the ability for continuous and reversible water uptake has been attributed to the presence of residual water in non-effloresced, (quasi-)liquid particles Prenni et al, 2003;Mochida and Kawamura, 2004;Moore and Raymond, 2008;Zardini et al, 2008) or to the morphology or amorphous state of (quasi-)solid particles (Cohen et al, 1987;Onasch et al, 2000;Marcolli et al, 2004;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, micro-Raman spectroscopic systems have been employed to investigate the molecular interactions in supersaturated droplets of different inorganic species (Wang et al 2005;Li et al 2006;Dong et al 2007) and the polymorphic transformation of NH 4 NO 3 particles deposited on a hydrophobic substrate (Wu and Chan 2008). Such micro-Raman systems have also been used to study hygroscopicity and phase transitions of Ca(NO 3 ) 2 and Ca(NO 3 ) 2 /CaCO 3 (Liu et al 2008a), and ammonium sulfate-adipic acid mixtures (Yeung et al 2009). Moreover, spatial spectroscopic imagining has proved useful for the phase and chemical characterization of heterogeneous particles (Liu et al 2008a;Yeung et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Such micro-Raman systems have also been used to study hygroscopicity and phase transitions of Ca(NO 3 ) 2 and Ca(NO 3 ) 2 /CaCO 3 (Liu et al 2008a), and ammonium sulfate-adipic acid mixtures (Yeung et al 2009). Moreover, spatial spectroscopic imagining has proved useful for the phase and chemical characterization of heterogeneous particles (Liu et al 2008a;Yeung et al 2009). A similar technique that utilizes micro-FTIR to study the hygroscopic behavior of pure inorganic and sea-salt particles has also been reported (Liu et al 2008b).…”
Section: Introductionmentioning
confidence: 99%